OPTIMASI PENGGUNAAN LAHAN BERDASARKAN KELAS KESESUAIAN LAHAN UNTUK PENGEMBANGAN TANAMAN CABAI MERAH DI KABUPATEN JEMBER - Rindha Rentina Darah Pertami; Eliyatiningsih Eliyatiningsih; Abdurrahman Salim; Basuki Basuki (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Chilli (Capsicum annum L.) is a horticulture comodities that high demand because it has a high economic value. The demand of Chilli increase every year as the population grows and the industry grows which requires Chilli as raw materials. The productivity of red chili in Jember Regency is also low, which is only 87.68 quintals hectare-1. Fluctuations in red chili production that occurred in the Jember area were caused by several things including an unsupportive environment such as declining soil fertility, high pest attacks, and excessive use of pesticides. Therefore there is a need for agricultural development in order to be able to meet food needs and increase export opportunities to neighboring countries. The parameters observed in this study were secondary data from the soil unit map. The secondary data referred to are soil drainage, soil depth in cm, slope related to erosion, altitude, standing water, soil cation exchange capacity, and soil pH. The improvement efforts made to improve the land suitability class is by setting the spacing, giving organic matter, agricultural lime, P fertilization, cutting and filling the land with a mound terrace system or bench terrace to reduce soil erosion.